An ultrathin-barrier AlGaN/GaN heterostructure: a recess-free technology for the fabrication and integration of GaN-based power devices and power-driven circuits. (22nd March 2021) - Huang, Sen; Wang, Xinhua; Liu, Xinyu; Sun, Qian; Chen, Kevin J
Abstract: An AlGaN-recess-free, ultrathin-barrier (UTB) AlGaN (<6 nm)/GaN heterostructure is presented for the fabrication and integration of AlGaN/GaN enhancement/depletion-mode (E/D-mode) heterojunction field-effect transistors (HFETs), and metal–insulator-semiconductor HFETs (MIS-HFETs). The 2D electron gas in the access region of the UTB-AlGaN/GaN (MIS)HFETs can effectively be recovered by a low-pressure chemical-vapor-deposited SiNx passivation layer (LPCVD-SiNx ), which is capable of introducing about 2.75 × 10 13 cm −2 positive fixed charges at the LPCVD-SiNx /(Al)GaN interface. LPCVD-SiNx can also serve as a good gate insulator for D-mode MIS-HFETs. Using the self-terminating etching of LPCVD-SiNx on III-nitride as well as a low-damage remote plasma pretreatment, high uniformity E-mode HFETs and low-hysteresis E-mode MIS-HFETs have been fabricated using the GaN-on-Si platform. E/D-mode MIS-HFET inverters with a large logic swing have also been demonstrated on this platform. The UTB-AlGaN/GaN heterostructure is an attractive technology platform for the on-chip integration of power and RF devices with power-driven circuits for GaN-based smart power integrated circuits.